2010
DOI: 10.1051/0004-6361/201015408
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the close environment ofβCephei with the VEGA/CHARA interferometer

Abstract: Context. High-precision interferometric measurements of pulsating stars help to characterize their close environment. In 1974, a close companion was discovered around the pulsating star β Cep using the speckle interferometry technique, and features at the limit of resolution (20 milli-arcsec or mas) of the instrument were mentioned that may be due to circumstellar material. β Cep has a magnetic field that might be responsible for a spherical shell or ring-like structure around the star as described by the MHD … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…The close environment of β Cep was recently investigated with interferometry by Nardetto et al (2011) with a spatial resolution of 1 mas. They concluded that a circular ring (instead of a uniform disk) gives the best fit with a geometry and orientation similar to the magnetic equator, as described above, which is a remarkable result.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The close environment of β Cep was recently investigated with interferometry by Nardetto et al (2011) with a spatial resolution of 1 mas. They concluded that a circular ring (instead of a uniform disk) gives the best fit with a geometry and orientation similar to the magnetic equator, as described above, which is a remarkable result.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Enfin, en étudiant l'environnement de l'étoile prototype des β Céphéides, nous avons découvert à l'aide de l'instrument visible VEGA/CHARA un environnement visible contribuant pour 23 ± 2% du flux. Mais la situation semble a priori différente de celle de δ Cep dans la mesure où un champ magnétique pourrait être responsable du confinement d'un disque en co-rotation autour de l'étoile (Nardetto et al 2011b) (voir l'annexe T).…”
Section: Une Piste De Recherche : La Comparaison Avec Les Autres Type...unclassified
“…It stands at 7σ from the relation. It is a β Cepheid and the photometric contamination by a surrounding environment and/or a close companion is not excluded (Sadsaoud et al 1994;Nardetto et al 2011).…”
Section: A Revised Sbc Relation For Late-and Early-type Starsmentioning
confidence: 99%